Ein Haus wie ich: die gebaute Autobiographie in der Moderne (unter Mitarbeit von Katharina Siebenmorgen) - Siebenmorgen, Katharina; Pisani, Salvatore; Oy-Marra, Elisabeth (Mainzer historische Kulturwissenschaften, 2014)
The classical places for the self as a subject of reflection are diaries, memoirs, and letters. But in the modern age, the house is increasingly recognized as an "imprint of its inhabitant" ("Abdruck seines Bewohners", Walter Benjamin). This points towards a new, privileged form of expropriation of the ego in architecture. In this interdisciplinary anthology, a very diverse and exciting picture is drawn of how language and subject expand their territory to include the house, and how life writing and life building complement each other. A conclusion that unites all the contributions and that reads surprisingly pre-modern: The ego inhabits a house, but the house also inhabits the ego.
Gesehen am 05.12.2016
Keywords: Geschichte 1800-2014; Architektur; Künste; Geschichte 1790-2014; Das Autobiografische